Methodological Issues of Qualitative Research on End-of-Life Care Among Older Korean Immigrants in the United States - Hyeyoung K. Park; Cristina C. Hendrix; Sharron L. Docherty; Kimberly S. Johnson; Ruth A. Anderson (International Journal of Qualitative Methods)
Qualitative research, rooted in interpretivism, is valuable for studying immigrant populations and understanding cultural influences on health behaviors. However, few studies have explored the methodological challenges of researching older Korean U.S. immigrants, particularly on sensitive topics like end-of-life care, which requires deep cultural understanding. This paper examines the challenges encountered during a pilot study on end-of-life care among older Korean U.S. immigrants. In addition to identifying key methodological obstacles, we highlight strategies to improve future research on sensitive topics within immigrant communities. Our study, informed by existing literature, faced unexpected challenges at every stage—recruitment, data collection, and analysis—each requiring careful adaptation. First, recruitment posed significant challenges. Many participants were hesitant to discuss end-of-life care due to cultural stigma, fearing it might invite misfortune. Some resisted signing consent forms, unfamiliar with Western research protocols and concerned about potential consequences. Others expected structured surveys rather than open-ended interviews, making engagement difficult. Second, conducting interviews brought additional hurdles. The setting needed to feel neutral, as medical or religious environments influenced responses. Language proficiency varied, requiring interpreters and adjusted phrasing. Discussions about end-of-life care sometimes triggered emotional distress, necessitating sensitivity and frequent check-ins. Third, data analysis required careful consideration. Translating nuanced Korean expressions into English was challenging, as some terms lacked direct equivalents. Case vignettes also needed thoughtful adaptation to ensure cultural relevance and avoid bias. Finally, participant feedback led to important revisions, reinforcing the value of involving participants throughout the research process. Engaging them early and reflecting on challenges afterward can improve study design and data quality. By addressing these methodological hurdles, this study provides practical insights for strengthening qualitative research on immigrant populations, particularly when exploring sensitive topics.